Multimodality in Malaysian Commercial Bank Brochures - Rajandran, Kumaran (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This paper uses multimodality to study communication. Communication does not only depend on language but also includes other modes, such as image. This paper focuses on advertising as it commonly uses multimodality to help it convey messages better. It studies two Malaysian commercial bank brochures and their use of image and language in print media to inform about and promote banking products to consumers. This suggests that both modes contribute to the communicative purposes of advertising. Two modes could deliver similar meanings to consumers differently and improve or strengthen the meanings of another mode. This paper tries to see the cooperation between image and language to create coherent brochures that interest consumers. It discusses several aspects of the image and language used to expose the messages both seem to convey. It then discusses the possible relations image and language have with each other. This paper argued that both image and language induce consumer interest in the product.